2021
DOI: 10.1186/s43055-021-00513-1
|View full text |Cite
|
Sign up to set email alerts
|

Can diffusion and T2 star-weighted magnetic resonance imaging aid in the diagnosis of ectopic endometrium?

Abstract: Background Endometriosis is a common gynecologic disorder characterized by the implantation of the endometrial tissue ectopically outside the endometrial cavity. It affects about 10% of females at the childbearing period and is estimated to be present up to 20–50% in women complaining of infertility. While laparoscopy is considered the mainstay for diagnosis, magnetic resonance imaging (MRI) is recognized as a useful tool for definitive diagnosis, pre-surgical planning, and determining whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…For this reason, it has recently been proposed in the literature that T2*W imaging can provide added diagnostic value to conventional MRI protocols in endometriosis detection [ 13 , 14 ]. Some authors suggested that susceptibility-weighted imaging (SWI) can contribute to the diagnosis of endometriomas by revealing T2*W signal voids in the cyst wall [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, it has recently been proposed in the literature that T2*W imaging can provide added diagnostic value to conventional MRI protocols in endometriosis detection [ 13 , 14 ]. Some authors suggested that susceptibility-weighted imaging (SWI) can contribute to the diagnosis of endometriomas by revealing T2*W signal voids in the cyst wall [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pin et al found that susceptibility-weighted sequences might improve the diagnostic performance of conventional MRI protocol in DIE assessment, with an increase in sensitivity (from 88.2% to 94.1%) and specificity (from 68.8% to 73.3%) [ 22 ]. In a recent publication, the addition of T2*W sequences to MRI protocols revealed even more favourable results: the sensitivity improved from 65.4% to 96.15%, while the specificity improved from 71.4% to 85.7% [ 14 ]. Nevertheless, in this study both readers were highly experienced radiologists, which may represent a limitation to the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the elasticity of the pelvic floor muscles becomes poor, the internal organs of the pelvic floor cannot maintain their normal positions, and the corresponding functions are impaired [ 17 ]. It is the only way to display the trajectory of muscle fiber bundles in vivo through the principle of anisotropy in the diffusion movement of water molecules in tissues [ 18 ] because the microstructure of tissue specimens will inevitably change during the processing process, resulting in geometric deformation. DTI adopts the cross-sectional spin echo-echo planar imaging (SE-EPI) technology, in which there are many parameters, and the most used are the diffusion sensitivity coefficient (b), the eigenvalues ( λ 1 , λ 2 , λ 3 ), average dispersion rate, fractional anisotropy, and apparent diffusion coefficient [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…MRI is more sensitive in diagnosis of origin, composition, shape, and lesion enhanced pattern specify the diagnosis differences [8]. Diffusion-weighted (DW) MRI is based on water molecules random movement within different tissues [9]. MRI has high tissue contrast and can be used to evaluate peritoneal deposits, metastatic lesions, tumour recurrence, and treatment response when combined with apparent diffusion coefficient (ADC) mapping [10].…”
Section: Introductionmentioning
confidence: 99%